2019
DOI: 10.1177/0886260519860889
|View full text |Cite
|
Sign up to set email alerts
|

Individual Moral Disengagement and Bullying Among Swedish Fifth Graders: The Role of Collective Moral Disengagement and Pro-Bullying Behavior Within Classrooms

Abstract: School bullying is a complex social and relational phenomenon with severe consequences for those involved. Most children view bullying as wrong and recognize its harmful consequences; nevertheless, it continues to be a persistent problem within schools. Previous research has shown that children’s engagement in bullying perpetration can be influenced by multiple factors (e.g., different forms of cognitive distortions) and at different ecological levels (e.g., child, peer-group, school, and society). However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
3
23
0
7
Order By: Relevance
“…Moreover, at the class-level, it was found that peer aggression was more likely in school classes characterized by higher levels of collective moral disengagement. These findings have been subsequently confirmed in a few studies conducted in other countries, such as Sweden (Bjärehed et al, 2019;Thornberg et al, 2021) andCzech Republic (Kollerová et al, 2018). However, almost all the existing empirical evidence is based on cross-sectional data.…”
Section: Collective Moral Disengagement and Aggressive Behaviormentioning
confidence: 63%
“…Moreover, at the class-level, it was found that peer aggression was more likely in school classes characterized by higher levels of collective moral disengagement. These findings have been subsequently confirmed in a few studies conducted in other countries, such as Sweden (Bjärehed et al, 2019;Thornberg et al, 2021) andCzech Republic (Kollerová et al, 2018). However, almost all the existing empirical evidence is based on cross-sectional data.…”
Section: Collective Moral Disengagement and Aggressive Behaviormentioning
confidence: 63%
“…The bullying phenomenon has been studied since the early 1970s [1,2]. Various researchers worldwide have agreed that bullying is a phenomenon increasingly present and that it has become a worrying social problem in educational, organizational, or interpersonal settings [3][4][5][6][7][8]. In recent years, with technology development, a new form of bullying emerged, namely cyberbullying, also known as electronic harassment or Internet harassment.…”
Section: Bullying and Cyberbullyingmentioning
confidence: 99%
“…Students involved in situations of school aggression engage in the most frequent moral disengagement arguments. Thus, prevention at primary school is necessary [ 34 ]. Consequently, we must promote social integration and minimize situations of school violence.…”
Section: Discussionmentioning
confidence: 99%